Analysis of Occupational Safety And Health in The Construction Project of Integrated Lecture Building - Dimas Aji Purnomo; Harliwanti Prisilia (Universitas Islam Raden Rahmat, Malang, 2025)
Occupational safety and health (OSH) is an important aspect in the implementation of construction projects, especially building projects that involve various high-risk activities. This research aims to analyze the implementation of the OHS system in building projects, identify potential hazards, and evaluate the effectiveness of mitigation efforts that have been made. The research method used is a quantitative and qualitative approach through field observations, interviews with workers, and analysis of related documents. The results show that the implementation of OHS still faces a number of challenges, such as lack of compliance with safety procedures, limited OHS facilities, and low levels of worker awareness of the importance of OHS. Nevertheless, some mitigation efforts, such as regular training and the use of personal protective equipment (PPE), have proven effective in reducing the risk of work accidents. This study recommends increased supervision, provision of adequate OHS facilities, and educational campaigns to build a safety culture in the work environment. The findings are expected to make a positive contribution to improving occupational safety and health on construction projects in Indonesia.